The mechanism and experimental study on the interference of high voltage lines to navigation system. (4th February 2019) - Fan, Linjing; Pan, Xuchao; Huang, Zhengxiang; Zu, Xudong
Summary: This essay conducts the mechanism analysis and experimental study on the interference of high voltage lines to the navigation system of UAV and shows that the essence of the interference is that air becomes corona plasma after the ionization under high voltage. In addition, when GPS signals pass through this area, some frequency channel will be absorbed. Therefore the propagation of electromagnetic waves is prevented. The UAV tries to get GPS positioning signal by flying through high voltage area in a low height, resulting in the loss of GPS signal received by the navigation system. Through the measurement and comparison of the electromagnetic wave spectrum traveled through corona plasma, the corona plasma's absorbing of electromagnetic wave is observed.